White Spot Syndrome Virus: A Detailed Review of Early Infection Events, Structural Protein Trafficking, and Innate Immune Evasion - Ling‐Ke Liu; Shan‐Shan Jing; Hai‐Peng Liu (Reviews in Aquaculture, 2025)
White spot syndrome virus (WSSV), the highly pathogenic double‐stranded DNA virus affecting crustaceans particularly shrimp and crayfish, has been causing severe diseases that result in significant economic losses in aquaculture. Despite various treatment efforts, current methods remain inadequate in effectively controlling the onset and transmission of the disease, underscoring the urgent need for innovative and efficient control and therapeutic strategies. Successful WSSV infection, along with the production of essential viral components, depends on continuous viral evolution, which serves as a key strategy to manipulate the host cellular environment, including host‐intrinsic factors and systems, as well as the antiviral immune responses. Research to date has primarily focused on WSSV structural characterization, initial cellular events following infection, functional analysis of viral components in regulating antiviral signaling pathways, and host cellular responses elicited by viral invasion. These studies shed light on critical pathogenic processes, including viral entry and intracellular transport events, trafficking of expressed viral structural proteins, and immune evasion mechanisms driven by virus‐host interaction. This review provides a comprehensive summary of recent progress in the development of WSSV infection cell models and elucidation of innate immune evasion strategies driven by virus‐host interplay. By consolidating current knowledge, it aims to enhance our understanding of WSSV pathogenesis and lay a solid foundation for development of innovative therapeutic approaches.